1983
DOI: 10.1152/jappl.1983.54.2.582
|View full text |Cite
|
Sign up to set email alerts
|

Muscle fiber composition and blood ammonia levels after intense exercise in humans

Abstract: The relationship between fiber type composition and the increase in blood ammonia was examined following a maximal O2 consumption (VO2max) test. Muscle biopsies were taken from the middle portion of the vastus lateralis for determination of fiber type percentages. Two subject groups were selected on the basis of a high (HST) or low (LST) percentage of slow-twitch fibers and compared for blood ammonia and lactate levels after exercise at work loads of approximately 85 and 110% of VO2max. An inverse relationship… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
27
0

Year Published

1987
1987
2008
2008

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(33 citation statements)
references
References 0 publications
6
27
0
Order By: Relevance
“…Probably, the decreased blood ammonia levels in hypoxia can be explained by the significant reduction in time to exhaustion and the concomitantly decreased total ATPbreakdown. Similar to previous reports of Dudley et al (1983), Ravier et al (2006), and Taylor and Bronks (1996), a significant correlation between blood lactate and ammonia concentration was observed in normoxia (R = 0.597, P < 0.001). In contrast to the findings of Taylor and Bronks (1996), who reported concurrent increases in lactate and ammonia concentration during incremental cycle ergometry, not only in normoxia but also in hypoxia (FiO 2 0.135), maximal capillary lacate and ammonia concentrations were not significantly correlated in the present study (R = 0.144, P = 0.60 in hypoxia).…”
Section: Discussionsupporting
confidence: 90%
“…Probably, the decreased blood ammonia levels in hypoxia can be explained by the significant reduction in time to exhaustion and the concomitantly decreased total ATPbreakdown. Similar to previous reports of Dudley et al (1983), Ravier et al (2006), and Taylor and Bronks (1996), a significant correlation between blood lactate and ammonia concentration was observed in normoxia (R = 0.597, P < 0.001). In contrast to the findings of Taylor and Bronks (1996), who reported concurrent increases in lactate and ammonia concentration during incremental cycle ergometry, not only in normoxia but also in hypoxia (FiO 2 0.135), maximal capillary lacate and ammonia concentrations were not significantly correlated in the present study (R = 0.144, P = 0.60 in hypoxia).…”
Section: Discussionsupporting
confidence: 90%
“…There is an inverse relationship between the percentage of slow-twitch fibers (%ST) and the increase in blood ammonia after intense exercise (Dudley, Staron, Murray, Hagerman, & Luginbuhl, 1983). This is consistent with the fact that glycolytic type lIb fiber is rich in AMP deaminase, the major source of ammonia during intense exercise.…”
Section: Sprinting Exercisesupporting
confidence: 78%
“…Activating AMP deaminase results in a large amount of ammonia in the blood. During maximal exercise, blood ammonia levels increase with a higher %IT (Dudley et al, 1983). At low workloads, ST fibers low in AMP deaminase are mainly used (Gollnick & Sembrowich, 1977).…”
Section: Muscle Fiber Compositionmentioning
confidence: 99%
“…It has been demonstrated in humans that the activity of the PNC and blood ammonia production is predominantly a reflection of fast twitch (type II) fibre activity during short-term intense exercise [27]. DUDLEY et al [28] reported an inverse relationship between the proportion of slow twitch (type I) fibres of the vastus lateralis muscle and ammonia increase during intense exercise in healthy subjects. The current findings of an early increase in plasma ammonia in incremental exercise in subjects with COPD suggest that fast twitch fibre recruitment is occurring at low WRs in this population.…”
Section: Discussionmentioning
confidence: 99%